Management of Economic Resources through the Development Policy - Sanusi, Anwar; Sudarwati, Ririn; Harsono, H.; Kholifah, Siti; Hendarto, Totok; Budiyanto, Didik (International Journal of Psychosocial Rehabilitation, 2020)
Policy directions to manage the economic resources in 2020-2024 include Fulfilling energy needs by prioritizing the increase of renewable energy (EBT) that will be implemented with the strategy of (1) accelerating the development of renewable energy generation; (2) increasing the supply of biofuels; (3) improving the implementation of conservation and energy efficiency; (4) increasing the fulfillment of energy for the industry; (5) developing EBT supporting industries.The future utilization of natural gas and coal resources for industry and electricity will focus on (1) gas utilization from the Aceh Block A field, East Natuna, Jambaran Tiung Bumi (East Java), Tangguh Train 3 and Asap-Kido-Merah (West Papua), and Abadi (Maluku); and (2) coal utilization from South Sumatra, South Kalimantan and East Kalimantan. Energy supply for industry and electricity will also be fulfilled through the development of renewable energy potential in Industrial Estates combined with the available energy. This supply pattern will focus on Industrial Estates in northern Sumatra, southern Sumatra, Java, eastern Kalimantan, northern and southern Sulawesi, North Maluku, and West Papua.